Fatal amyloid formation in a patient’s antibody light chain is caused by a single point mutation - Kazman, Pamina; Vielberg, Marie-Theres; Pulido Cendales, María Daniela; Hunziger, Lioba; Weber, Benedikt; Hegenbart, Ute; Zacharias, Martin; Köhler, Rolf; Schönland, Stefan; Groll, Michael; Buchner, Johannes (eLife, 2020)
In systemic light chain amyloidosis, an overexpressed antibody light chain (LC) forms fibrils which deposit in organs and cause their failure. While it is well-established that mutations in the LC’s VL domain are important prerequisites, the mechanisms which render a patient LC amyloidogenic are ill-defined. In this study, we performed an in-depth analysis of the factors and mutations responsible for the pathogenic transformation of a patient-derived λ LC, by recombinantly expressing variants in E. coli. We show that proteolytic cleavage of the patient LC resulting in an isolated VL domain is essential for fibril formation. Out of 11 mutations in the patient VL, only one, a leucine to valine mutation, is responsible for fibril formation. It disrupts a hydrophobic network rendering the C-terminal segment of VL more dynamic and decreasing domain stability. Thus, the combination of proteolytic cleavage and the destabilizing mutation trigger conformational changes that turn the LC pathogenic.
Gesehen am 11.03.2020